Novel Therapies Against Aggressive and Recurrent Epithelial Cancers by Molecular Targeting Tumor- and Metastasis-Initiating Cells and Their Progenies - Mimeault, Murielle (2010)
A growing body of experimental evidence has revealed that the highly tumorigenic cancer stem/progenitor cells endowed with stem cell-like properties might be responsible for initiation and progression of numerous aggressive epithelial cancers into locally invasive, metastatic and incurable disease states. The malignant transformation of tissue-resident adult stem/progenitor cells or their progenies into tumorigenic and migrating cancer stem/progenitor cells and their resistance to current cancer therapies have been associated with their high expression levels of specific oncogenic products and drug resistance-associated molecules. In this regard, we describe the tumorigenic cascades that are frequently activated in cancer stem/progenitor cells versus their differentiated progenies during the early and late stages of the epithelial cancer progression. The emphasis is on the growth factor signaling pathways involved in the malignant behavior of prostate and pancreatic cancer stem/progenitor cells and their progenies. Of clinical interest, the potential molecular therapeutic targets to eradicate the tumor- and metastasis-initiating cells and their progenies and develop new effective combination therapies against locally advanced and metastatic epithelial cancers are also described.